Paparan Polusi Udara di Permukiman Padat Perkotaan di Indonesia dan Hubungannya dengan ISPA pada Kelompok Rentan: Scoping Review - Farah Aini Fatimah; Triana Srisantyorin; Suherman Jaksa (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Air pollution poses a major environmental health threat in Indonesia, particularly in densely populated urban settlements, where vulnerable groups such as children under five, the elderly, and outdoor workers face an elevated risk of Acute Respiratory Infections (ARI). This scoping review aimed to identify and synthesize scientific evidence on the association between air pollution exposure in urban settlements in Indonesia and ARI incidence among vulnerable populations. Following PRISMA guidelines, a systematic literature search was conducted across PubMed, Scopus, and Google Scholar databases, including studies on air pollution and ARI in Indonesia or relevant developing countries published between 2015 and 2025. Of 733 articles identified, 38 studies met the inclusion criteria. The average PM2.5 concentration in Jakarta reached 42.5 µg/m³, exceeding WHO standards. Air pollution in densely populated urban areas of Indonesia significantly increases ARI risk among vulnerable groups, necessitating integrated interventions including emission control, clean fuel promotion, and improved household ventilation to protect public health.